OPTIMALISASI PENDAPATAN TANAH KAS DESA DI DESA BATANG BATINDIH KECAMATAN RUMBIO JAYA KABUPATEN KAMPAR TAHUN 2009-2013 - Setiawan, Yoga; Marta, Auradian (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
In the current era of village autonomy, PADesa an important benchmark for the village's ability to organize and menujudkan village autonomy, also reflects the independence of a village because PADesa is a source of pure acceptance of the village. However, if walking is not optimal PADesa it will be difficult for the village to carry out the process of governance and development independently, without the support of other parties. This occurred in the village of Batang Batindih in optimizing its income receipts. Especially PADesa sourced from Land Kas village, so the village was not optimal in receiving the income generated from the land of the village of Kas. The purpose of this study was to determine the constraints and efforts in optimizing the village of Batang Batindih Pades sourced from Cash Land Village.The theory used in this research is autonomy village, Policies, and Institutions. The method used in this study is a qualitative approach. The technique used for collecting data are observation, interview, and documentation, then analyzed using descriptive analysis method. Source interviews in this study came from informants by using purposive sampling technique Informanyaitu parties know the constraints and the village of Batang Batindih efforts in optimizing the potential of the ground the village treasury.Results from this study indicate that the village of Batang Batindih has a huge potential source of income for villagers who came from the village of Kas Land. Constraints in optimizing cash income rural land in the village of Batang Batindih form; Village Regulation (Perdes) which has not been ratified, Perdes here synchronizes with the theory of Village Autonomy. The main key of Village Autonomy participation, proactive and community initiative and self-reliance. Implementation of institutional authority have not been up that includes; Low competence village government officials, as well as the level of public education is still low. Authority here synchronize with the policy theory. There are several characteristics of policies, namely; there must be tujuanya policy, the policy does not stand alone, the policy is what the government and the policy should be based on the law. Institutional capacity is not maximized village which includes; lack of capacity, initiative, creativity and tenggung responsible for the ground the village treasury. Here institutional synchronizes with institutional theory There are five (5) opinion regarding the institutional system; communications systems, economic systems, the system agreement,the system of authority and power sharing and ritual system to maintain social ties that ada.Sedangkan efforts to address these obstacles in the form; Increase community participation in the form; deliberation, rapat.partisipasi is associated with the theory of village autonomy. Enhance Institutional Capacity in the form of village government; Training, discussion. Institutional is associated with institutional theory. And empower communities to participate in the Cash Land Village. Empower is associated with the policy theory.Keywords: ground the village treasury, revenue village.